Utilization of QGIS 3.22 with a Spatial Approach in Assessing Tsunami Risk on Small Islands in Ternate City - Sabaruddin Sabaruddin; Rusman Rasyid (Universitas Khairun, 2023)
The city of Ternate is an archipelago city consisting of 5 small islands and 3 large islands. This city is prone to earthquake activity because it is right above the active volcano, namely Mount Gamalama. in 2012 there was an earthquake that caused severe damage to residential areas. This incident was caused by local tectonic earthquakes occurring 39 times, distant tectonic earthquakes occurring 432 times, and tectonic earthquakes being felt 5 times. It is not surprising that in the future this city will experience a tsunami as a result of the activity of mount gamalama because geographically this city is an archipelago city where activities between cities and districts depend on sea transportation. The purpose of this study is to model a tsunami with a height of 30 meters in the city of Ternate. Based on the results of spatial data, the impact of the tsunami occurred that almost all districts on the island of Ternate would sink. The most severe sub-districts are the sub-districts of Central Ternate city, North Ternate city and South Ternate city. Meanwhile, for the Ternate island sub-district, the impact was not too significant.